Research on the Impact of Store Sales Share on Consumer Purchase Intentions in the Catering Industry - Xue, Chufan (Transactions on Economics, Business and Management Research, 2024)
Over the past few years, with the rapid development of the catering industry and the continuous expansion of the market, consumer demands have become increasingly diverse. For catering businesses to develop steadily amidst fierce industry competition, it is crucial to enhance store sales share and boost consumer purchase intentions. This can be achieved by grounding strategies in industry trends and the unique characteristics of the business. As consumers’ material standards have risen, higher expectations have been set for brands, pricing, menu uniqueness, and service quality. Therefore, catering enterprises should clearly define their brand positioning, employ diverse measures to enhance brand image and recognition, understand the varying impacts of store sales share on purchase intentions across different types of catering businesses, innovate upon existing pricing strategies, emphasize the uniqueness of the menu, and bring fresh experiences to consumers. Additionally, leveraging modern information technology and digital marketing can expand brand impact, establish a positive corporate image, and win consumer trust.